Cidades sustentáveis: princípios orientadores de educação para a sustentabilidade em contextos urbanos - Grohe, Sandra Lilian Silveira (Universidade do Vale do Rio dos Sinos, 2021)
This thesis aims, from comprehensive analysis, to identify the guiding principles of education for sustainability in urban contexts. In an attempt to identify the principles, there was a fundamental question during the research: When does a city educate for sustainability? For this purpose, it has been necessary to trace the course of Brazil for promoting sustainable cities, starting from international for national movements, from global agendas and their local implementations, as well as, it was necessary transit by different definitions for sustainable cities, educator cities, sustainability and education for sustainability. Searching for answers beyond the documented, in 2019, cities of southern Brazil, Colombo (Paraná) and São Leopoldo (Rio Grande do Sul), were visited for the realization of comprehensive interviews. In this transition, between theory and empiry, the principles of education, governance and mobilization have been identified. The principle of Education was recognized as the main focus in a city that aims to be sustainable. That means educating for life in all dimensions, for transformation, for sustainable development and for the relations. In this sense, it is essential the permanence of a strong environmental education, based on policies, researches, educational programs and projects for sustainability. In the principle of governance it has been emphasized the relevance of the political desire for the implementation of education for sustainability, as well as the importance of a sensitive, holistic and horizontal look at the territory. The city that governs for sustainability is attentive and inserted in the global agreements and in the intercity alliances. It encourages the participation, the creation of spaces of expression, of dialogues and of critical thinking. The governor that intends to contribute for a city to be more sustainable, needs to give continuation on the policies, programs, projects and on successful actions of previous governments, avoiding ephemeral processes. Already at the beginning of the mobilization, the sensibilization has been identified as facilitator of the experiences of belonging to the city, closely related to disclosure, communication, information and to visibility. In this sense, one of the findings was related to the position of dependence, responsibility of the population due to disinformation, lack of environmental consciousness and due to community practices. These three principles have been pointed out as those which may contribute to the transformation of cities, having education as one of the main axis, governance with a sensitive and global look at the territory and the mobilization aimed at new beginnings, starting from the ones experienced. They are not occluded principles, on the contrary, they must be associated with other principles inherent to education, sustainability and the city. Lastly, these principles need to be analyzed, explored and expanded according to each reality, meanwhile they must be understood as possibilities for local and, consequently, global transformation.
Keywords: Educação; Sustentabilidade; Cidades sustentáveis; Education; Sustainability; Sustainable cities; ACCNPQ::Ciências Humanas::Educação